2011
DOI: 10.1111/j.1477-9552.2011.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

The Elusive Price Premium for Ecolabelled Products: Evidence from Seafood in the UK Market

Abstract: Ecolabelling is an increasingly important tool used in the promotion of sustainable forestry and fishery products around the world. Whether the consumer is actually paying a price premium for ecolabelled products is of fundamental importance as it indicates a return on the investment of sustainable practices, providing an incentive for producers to undertake such practices. This article seeks to address the question of whether or not an actual premium is being paid by consumers for ecolabelled seafood by condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
230
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(237 citation statements)
references
References 32 publications
5
230
0
2
Order By: Relevance
“…Therefore, at least, some of the consumers have to be convinced that European products are worth higher prices. Recent research shows that the promotion of sustainability in seafood bears potential for product differentiation and thereby higher premiums and market shares (Ankamah-Yeboah et al, 2016;Asche, Larsen, Smith, SognGrundvåg, & Young, 2015;Jaffry, Pickering, Ghulam, Whitmarsh, & Wattage, 2004;Roheim, Asche, & Santos, 2011). Earlier research stressed that a particular consumer segment which appreciates additional ethical values of products and is willing to pay higher prices exists (Altintzoglou et al, 2010;Feucht & Zander, 2015;Kalshoven & Meijboom, 2013;Lasner & Hamm, 2014;Mauracher, Tempesta, & Vecchiato, 2013;Risius et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, at least, some of the consumers have to be convinced that European products are worth higher prices. Recent research shows that the promotion of sustainability in seafood bears potential for product differentiation and thereby higher premiums and market shares (Ankamah-Yeboah et al, 2016;Asche, Larsen, Smith, SognGrundvåg, & Young, 2015;Jaffry, Pickering, Ghulam, Whitmarsh, & Wattage, 2004;Roheim, Asche, & Santos, 2011). Earlier research stressed that a particular consumer segment which appreciates additional ethical values of products and is willing to pay higher prices exists (Altintzoglou et al, 2010;Feucht & Zander, 2015;Kalshoven & Meijboom, 2013;Lasner & Hamm, 2014;Mauracher, Tempesta, & Vecchiato, 2013;Risius et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The two articles most relevant to our paper are Roheim et al [41] applying an hedonic price function approach to scanner data on the sale of frozen, processed Alaskan Pollock in the London metropolitan market to estimate a statistically significant price premium for Marine Stewardship Council certification, and…”
Section: Introductionmentioning
confidence: 99%
“…In the revealed preference literature, hedonic price models [8,41,42,12,27], demand system [47] and case study [39] approaches have been used to estimate relative values for seafood product attributes such as catch method, fishing gear choice, country of origin, product color (of salmon), and environmental sustainability. The two articles most relevant to our paper are Roheim et al [41] applying an hedonic price function approach to scanner data on the sale of frozen, processed Alaskan Pollock in the London metropolitan market to estimate a statistically significant price premium for Marine Stewardship Council certification, and…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies have focused on capture fisheries and only a few on farmed seafood [6]. Earlier work has either: (a) applied an experimental approach using contingent valuation to estimate consumers' willingness to pay for eco-labeled seafood [7][8][9][10]; (b) examined consumers' attitudes towards eco-labeling of seafood [11][12][13]; (c) more generally explored the perceived importance of sustainability and ethics related to seafood [14,15]; or (d) used market data to investigate whether there is a price premium for eco-certified seafood [16,17]. While this work has substantially increased our understanding of what factors predict willingness to purchase sustainable seafood, to our knowledge, no study has yet investigated how consumers' self-reported purchasing behavior of eco-labeled seafood is correlated with environmental knowledge and other internal factors expected to predict pro-environmental consumption.…”
Section: Introductionmentioning
confidence: 99%